Report of Visit to Spain, Autumn, 1947 (1947)
1947 038-0010-002 Capt. Turner accompanied me on a number of my visits. His address is c/o St. Christopher School, Letchworth, Herts, at which school he is a schoolmaster. He and his wife were on a visit to Spain to see her widowed mother and other members of the family. This short report of my visit is passed on in the hope that the evidences it contains of the appalling treatment of those whose chief crime was that they had dared to resist the overthrow of their democratically elected republican government, may lead to some clear declaration in regard to the Spanish situation on behalf of the Government which would (1) at least inspire hope and faith of Spanish democrats in our sympathy and, more, (2) our assurance of diplomatic action when practical which may help to secure recognition of basic human and political rights. I believe, with many others, that when the majority of the business and financial supporters of the present regime can understand that a fuller progressive development in business and economic relationships could be expected to follow such recognition, there would be an added incentive for helping to secure the political changes which all good democrats so intensely desire to see effected. I conclude by asking that my name and the mention of "Basque refugees" in connection with this visit should be omitted from any public reference to it, as the sources of the information could then be easily traced, with possible dire consequences. I will, however, add some of my "credentials". R. WEST. Assistant Clerk, Reigate Society of Friends (Quakers). Labour member Reigate Borough Council (14 years). Member Labour Party (30 years). 292/946/38/10(II)